Infectious disease risk in asbestos abatement workers - Lange John H; Mastrangelo Giuseppe; Cegolon Luca (BMC, 2012)
Abstract Background The current literature reports increased infectious disease occurrence in various construction occupations, as an important contributor to morbidity and mortality arising from employment. These observations should be expanded to asbestos abatement workers, as the abatement can create an environment favorable for bacterial, viral and fungal infections. Discussion Asbestos abatement work employs activities resulting in cuts, blisters and abrasions to the skin, work in a dirty environment and exposure to dust, mists and fumes. Furthermore, this population exhibits a high smoking rate which increases the risk of chronic obstructive pulmonary disease and respiratory infections. In addition, these workers also commonly employ respirators, which can accumulate dirt and debris magnifying exposure to microbes. Use of respirators and related types of personal protective equipment, especially if shared and in the close environment experienced by workers, may enhance communicability of these agents, including viruses. Summary Abatement workers need to be provided with information on hazards and targeted by appropriate health education to reduce the infection risk. Epidemiological studies to investigate this risk in asbestos removers are recommended.